Biodegradation of Hazardous and Special Products - Chamy, Rolando; Rosenkranz, Francisca (IntechOpen, 2013)
This book contains a collection of different research activities that include the biodegradation compounds with contaminant characteristics and special products of different interests as an added value product or that allows following up various biological processes. The chapters consider the degradation of contaminant compounds generated by industrial activities, i.e., oil industry by-product compounds and halogen compounds or compound generated by natural phenomena such as tsunamis, which require interventions to recover damaged soils. In addition, the book contains chapters that involve special product degradation processes such as chlorophyll, which corresponds to a biological process indicator as photosynthesis.